Low oxidative stress during mitochondrial recovery from anoxia in Artemia franciscana, an invertebrate extremophile - Daniel A. Arabie; Olivia G. Moncrief; Samantha M. Shirmer; Steven C. Hand (Journal of Comparative Physiology B, 2025)

Neuromodulation by repetitive paired-pulse TMS at late I-wave intervals in older adults - Wei-Yeh Liao; Brodie J. Hand; Giuseppe Rinaldi; John G. Semmler; George M. Opie (Experimental Brain Research, 2025)
The efficacy of indirect (I) wave periodicity repetitive transcranial magnetic stimulation (iTMS) on the excitability of primary motor cortex (M1) in young adults can be modified by changing the late I-wave interval. Given that late I-wave activity is altered in older adults, this could contribute to age-related changes in M1 plasticity. To assess this possibility, the present study investigated the effects of iTMS using three late I-wave intervals (4.0, 4.5, and 5.0 ms) on M1 excitability in 17 older adults (69.6 ± 5.7 years; 10 females), which was compared to findings obtained previously in 17 young adults (27.2 ± 6.4 years, 12 females). Changes in M1 excitability were assessed using motor evoked potentials (MEPs) recorded from the right first dorsal interosseus to index single-pulse MEP 1.0mV and paired-pulse short-interval intracortical facilitation (SICF). To increase sensitivity to different intracortical circuits, both measures were also recorded using posterior-anterior (PA) and anterior-posterior (AP) TMS currents. Within older adults, PA MEP 1.0mV and SICF were facilitated following iTMS (both P < 0.0001) and these were not different between iTMS ISIs (both P > 0.077). In contrast, AP MEP 1.0mV and SICF were potentiated by iTMS 4.0 and iTMS 5.0 (both P < 0.023). iTMS 5.0 potentiation of AP circuits was also increased in older adults compared to young adults (both P < 0.004). These results suggest complex, timing-dependent effects of advancing age on the plasticity of the late I-wave circuits.

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Investigating the Effects of Repetitive Paired-Pulse Transcranial Magnetic Stimulation on Visuomotor Training Using TMS-EEG - Ryoki Sasaki; Brodie J. Hand; Wei-Yeh Liao; John G. Semmler; George M. Opie (Brain Topography, 2024)
I-wave periodicity repetitive paired-pulse transcranial magnetic stimulation (iTMS) can modify acquisition of a novel motor skill, but the associated neurophysiological effects remain unclear. The current study therefore used combined TMS-electroencephalography (TMS-EEG) to investigate the neurophysiological effects of iTMS on subsequent visuomotor training (VT). Sixteen young adults (26.1 ± 5.1 years) participated in three sessions including real iTMS and VT (iTMS + VT), control iTMS and VT (iTMS Control + VT), or iTMS alone. Motor-evoked potentials (MEPs) and TMS-evoked potentials (TEPs) were measured before and after iTMS, and again after VT, to assess neuroplastic changes. Irrespective of the intervention, MEP amplitude was not changed after iTMS or VT. Motor skill was improved compared with baseline, but no differences were found between stimulus conditions. In contrast, the P30 peak was altered by VT when preceded by control iTMS ( P < 0.05), but this effect was not apparent when VT was preceded by iTMS or following iTMS alone (all P > 0.15). In contrast to expectations, iTMS was unable to modulate MEP amplitude or influence motor learning. Despite this, changes in P30 amplitude suggested that motor learning was associated with altered cortical reactivity. Furthermore, this effect was abolished by priming with iTMS, suggesting an influence of priming that failed to impact learning.

Defense against oxidative stress during mitochondrial transitions into anoxia for an invertebrate extremophile - Daniel A. Arabie; Olivia G. Moncrief; Samantha M. Shirmer; Steven C. Hand (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Utilising TMS-EEG to Assess the Response to Cerebellar-Brain Inhibition - R. Sasaki; B. J. Hand; W. Y. Liao; N. C. Rogasch; L. Fernandez; J. G. Semmler; G. M. Opie (The Cerebellum, 2022)
Cerebellar-brain inhibition (CBI) is a transcranial magnetic stimulation (TMS) paradigm indexing excitability of cerebellar projections to motor cortex (M1). Stimulation involved with CBI is often considered to be uncomfortable, and alternative ways to index connectivity between cerebellum and the cortex would be valuable. We therefore sought to assess the utility of electroencephalography in conjunction with TMS (combined TMS-EEG) to record the response to CBI. A total of 33 volunteers (25.7 ± 4.9 years, 20 females) participated across three experiments. These investigated EEG responses to CBI induced with a figure-of-eight (F8; experiment 1) or double cone (DC; experiment 2) conditioning coil over cerebellum, in addition to multisensory sham stimulation (experiment 3). Both F8 and DC coils suppressed early TMS-evoked EEG potentials (TEPs) produced by TMS to M1 ( P < 0.05). Furthermore, the TEP produced by CBI stimulation was related to the motor inhibitory response to CBI recorded in a hand muscle ( P < 0.05), but only when using the DC coil. Multisensory sham stimulation failed to modify the M1 TEP. Cerebellar conditioning produced changes in the M1 TEP that were not apparent following sham stimulation, and that were related to the motor inhibitory effects of CBI. Our findings therefore suggest that it is possible to index the response to CBI using TMS-EEG. In addition, while both F8 and DC coils appear to recruit cerebellar projections, the nature of these may be different.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Anatomical and biochemical studies of Spartium junceum infected by Xylella fastidiosa subsp. multiplex ST 87 - S. Falsini; C. Tani; G. Sambuco; A. Papini; P. Faraoni; S. Campigli; L. Ghelardini; G. Bleve; D. Rizzo; M. Ricciolini; I. Scarpelli; L. Drosera; et al. (Protoplasma, 2022)
Spartium junceum L. is a typical species of Mediterranean shrubland areas, also grown in gardens and parks as an ornamental. In recent years in Europe, S. junceum has been recurrently found to be infected by different subspecies and genotypes of the quarantine regulated bacterium Xylella fastidiosa (Xf). This work presents for the first time the anatomy of S. junceum plants that we found, by means of genetic and immunochemistry analysis, to be naturally infected by Xf subsp. multiplex ST87 (XfmST87) in Monte Argentario (Grosseto, Tuscany, Italy), a new outbreak area within the EU. Our anatomical observations showed that bacteria colonized exclusively the xylem conductive elements and moved horizontally to adjacent vessels through pits. Interestingly, a pink/violet matrix was observed with Toluidine blue staining in infected conduits indicating a high content of acidic polysaccharides. In particular, when this pink-staining matrix was observed, bacterial cells were either absent or degenerated, suggesting that the matrix was produced by the host plant as a defense response against bacterial spread. In addition, a blue-staining phenolic material was found in the vessels and, at high concentration, in the pits and inter-vessels. SEM micrographs confirmed that polysaccharide and phenolic components showed different structures, which appear to be related to two different morphologies: fibrillary and granular, respectively. Moreover, our LM observations revealed bacterial infection in xylem conductive elements of green shoots and leaves only, and not in those of other plant organs such as roots and flowers.

Motor cortex plasticity and visuomotor skill learning in upper and lower limbs of endurance-trained cyclists - Brodie J. Hand; George M. Opie; Simranjit K. Sidhu; John G. Semmler (European Journal of Applied Physiology, 2022)

Age-related changes in motor cortex plasticity assessed with non-invasive brain stimulation: an update and new perspectives - John G. Semmler; Brodie J. Hand; Ryoki Sasaki; Ashley Merkin; George M. Opie (Experimental Brain Research, 2021)

Remarkable anoxia tolerance by stoneflies from a floodplain aquifer - Rachel L. Malison; Bonnie K. Ellis; Amanda G. DelVecchia; Hailey Jacobson; Brian K. Hand; Gordon Luikart; H. Arthur Woods; Maribet Gamboa; Kozo Watanabe; Jack A. Stanford (Ecology, 2020)
Alluvial aquifers are key components of river floodplains and biodiversity worldwide, but they contain extreme environmental conditions and have limited sources of carbon for sustaining food webs. Despite this, they support abundant populations of aquifer stoneflies that have large proportions of their biomass carbon derived from methane. Methane is typically produced in freshwater ecosystems in anoxic conditions, while stoneflies (Order: Plecoptera) are thought to require highly oxygenated water. The potential importance of methane‐derived food resources raises the possibility that stonefly consumers have evolved anoxia‐resistant behaviors and physiologies. Here we tested the anoxic and hypoxic responses of 2,445 stonefly individuals in three aquifer species and nine benthic species. We conducted experimental trials in which we reduced oxygen levels, documented locomotor activity, and measured survival rates. Compared to surface‐dwelling benthic relatives, stoneflies from the alluvial aquifer on the Flathead River (Montana) performed better in hypoxic and anoxic conditions. Aquifer species sustained the ability to walk after 4–76 h of anoxia vs. 1 h for benthic species and survived on average three times longer than their benthic counterparts. Aquifer stoneflies also sustained aerobic respiration down to much lower levels of ambient oxygen. We show that aquifer taxa have gene sequences for hemocyanin, an oxygen transport respiratory protein, representing a possible mechanism for surviving low oxygen. This remarkable ability to perform well in low‐oxygen conditions is unique within the entire order of stoneflies (Plecoptera) and uncommon in other freshwater invertebrates. These results show that aquifer stoneflies can exploit rich carbon resources available in anoxic zones, which may explain their extraordinarily high abundance in gravel‐bed floodplain aquifers. These stoneflies are part of a novel food web contributing biodiversity to river floodplains.

Resubduction of lawsonite eclogite within a serpentinite-filled subduction channel - R. Tamblyn; M. Hand; L. Morrissey; T. Zack; G. Phillips; D. Och (Contributions to Mineralogy and Petrology, 2020)

Assembly and characterisation of a unique onion diversity set identifies resistance to Fusarium basal rot and improved seedling vigour - Andrew Taylor; Graham R. Teakle; Peter G. Walley; William E. Finch-Savage; Alison C. Jackson; Julie E. Jones; Paul Hand; Brian Thomas; Michael J. Havey; David A. C. Pink; John P. Clarkson (Theoretical and Applied Genetics, 2019)
Key message A unique, global onion diversity set was assembled, genotyped and phenotyped for beneficial traits. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers. Abstract Conserving biodiversity is critical for safeguarding future crop production. Onion ( Allium cepa L.) is a globally important crop with a very large (16 Gb per 1C) genome which has not been sequenced. While onions are self-fertile, they suffer from severe inbreeding depression and as such are highly heterozygous as a result of out-crossing. Bulb formation is driven by daylength, and accessions are adapted to the local photoperiod. Onion seed is often directly sown in the field, and hence seedling establishment is a critical trait for production. Furthermore, onion yield losses regularly occur worldwide due to Fusarium basal rot caused by Fusarium oxysporum f. sp. cepae . A globally relevant onion diversity set, consisting of 10 half-sib families for each of 95 accessions, was assembled and genotyping carried out using 892 SNP markers. A moderate level of heterozygosity (30–35%) was observed, reflecting the outbreeding nature of the crop. Using inferred phylogenies, population structure and principal component analyses, most accessions grouped according to local daylength. A high level of intra-accession diversity was observed, but this was less than inter-accession diversity. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers, confirming the utility of the diversity set for discovering beneficial traits. The onion diversity set and associated trait data therefore provide a valuable resource for future germplasm selection and onion breeding.

Projected changes in hailstorms during the 21st century over the UK - M. G. Sanderson; W. H. Hand; P. Groenemeijer; P. M. Boorman; J. D. C. Webb; L. J. McColl (International Journal of Climatology, 2015)
Hailstorms can pose a significant threat to society, by damaging property and disrupting livelihoods. An understanding of how hailstorm characteristics may change under a warming climate is therefore important for assessing the risk of hail damage for the insurance industry. A simple model of hailstone formation has been driven using meteorological data produced by a regional climate model (RCM) to project how hailstorm numbers and hailstone sizes could change during the 21st century in the UK . Evaluation of the modelled hailstone sizes, numbers and spatial distributions showed that they agreed reasonably well with observations. The effect of climate change on the numbers of damaging hailstorms in the UK (hailstones with diameters greater than 15 mm) was then investigated. A downward trend in the total number of damaging hailstorms during the 21st century was projected, with statistically significant trends for hailstones with diameters between 21 and 50 mm. Melting of hailstones made little contribution to the projected reductions. The results are subject to large uncertainties, some of which originate with the convective parameterization scheme used by the climate model.

Characterization of isolates that cause black rot of crucifers in East Africa - Joseph M. K. Mulema; Joana G. Vicente; David A. C. Pink; Alison Jackson; Duncan O. Chacha; Lusike Wasilwa; Zakary M. Kinyua; Daniel K. Karanja; Eric B. Holub; Paul Hand (European Journal of Plant Pathology, 2012)

The influence of genetic variation and nitrogen source on nitrate accumulation and iso-osmotic regulation by lettuce - Ian G. Burns; James Durnford; James Lynn; Sandy McClement; Paul Hand; David Pink (Plant and Soil, 2012)

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Identification of quantitative trait loci for resistance to Xanthomonas campestris pv. campestris in Brassica rapa - P. Soengas; P. Hand; J. G. Vicente; J. M. Pole; D. A. C. Pink (Theoretical and Applied Genetics, 2007)

Blue sucker stock characteristics in the upper Yazoo River basin, Mississippi, USA - G. R. Hand; D. C. Jackson (Fisheries Management and Ecology, 2003)
Blue sucker Cycleptus elongatus (L.) in the upper Yazoo River basin, Mississippi, USA was studied using overnight hoop net sets ( n = 4093) during 1988 and 1990–1998 to determine the influence of channel dredging. There were 264 blue suckers captured, ranging from 3 to 11 years of age. Length ranged from 265 to 700 mm and weight from 120 to 4700 g. Concurrent studies with smaller mesh hoop nets failed to capture any juvenile blue suckers. Catch‐per‐unit‐effort (CPUE: fish net −1 ) declined throughout the study in the Yalobusha River, a river subjected to channel dredging during 1988 and 1994. With the exception of limited hydraulic dredging in the Tallahatchie River, there was no dredging in the other Yazoo River tributaries, nor were there declines in blue sucker catch rates in these rivers. Throughout the upper Yazoo River basin, blue sucker stocks were dominated by adult fish, and there was little evidence of reproduction or recruitment. Conservation of the blue sucker in the upper Yazoo River basin should include actions that ensure the functional integrity of this floodplain river ecosystem and elimination of channel dredging throughout the basin.

Anoxia tolerance of con-familial tiger beetle larvae is associated with differences in energy flow and anaerobiosis - W. W. Hoback; J. E. Podrabsky; L. G. Higley; D. W. Stanley; S. C. Hand (Journal of Comparative Physiology B, 2000)

Physiological response to complex environments in annual Polygonum species of contrasting ecological breadth - S. E. Sultan; A. M. Wilczek; D. L. Bell; G. Hand (Oecologia, 1998)

Distribution of the bispyridinium oxime [14C] HI-6 in male and female rats - Paul M. Lundy; Brian T. Hand; Brian R. Broxup; George Yipchuck; Murray G. Hamilton (Archives of Toxicology, 1990)

The multipolar content of the human electrocardiogram - Leo G. Horan; R. Chris Hand; Nancy C. Flowers; Jennifer C. Johnson; Daniel A. Brody (Annals of Biomedical Engineering, 1976)